Crystal structure of a dithiocarbazate diester: E-bis(3-methylbenzyl)-1-(6-methylpyridin-2-yl)ethylidene-carbohydrazonod ithioate, C25H27N3S2 - Tayamon, S.; Tiekink, E.R.T.; Omar, S.A.; Ravoof, T.B.S.A.; Tahir, M.I.M.; Crouse, K.A. (De Gruyter Open, 2014)
C25H27N3S2, monoclinic, P2(1)/n (no. 14), a = 8.2943(4) angstrom, b = 8.5039(4) angstrom, c = 33.587(2) angstrom, beta = 95.921(4)degrees, V = 2356.4 angstrom(3), Z = 4, R-gt(F) = 0.0451, wR(ref)(F-2) = 0.1340, T = 150 K.